German rabbis in British exile : from 'Heimat' into the unknown - Zajdband, Astrid (2016)
The rich history of the German rabbinate came to an abrupt halt with the November Pogrom of 1938. The need to leave Germany became clear and many rabbis made use of the visas they had been offered. Their resettlement in Britain was hampered by additional obstacles such as internment, deportation, enlistment in the Pioneer Corps. But rabbis still attempted to support their fellow refugees with spiritual and pastoral care. The refugee rabbis replanted the seed of the once proud German Judaism into British soil. New synagogues were founded and institutions of Jewish learning sprung up, like rabbinic training and the continuation of Wissenschaft des Judentums. The arrival of Leo Baeck professionalized these efforts and resulted in the foundation of the Leo Baeck College in London. Refugee rabbis now settled and obtained pulpits in the many newly founded synagogues. Their arrival in Britain was the catalyst for much change in British Judaism, an influence that can still be felt today.